Effect of detergents on membrane-associated glucan synthetase from Paracoccidioides brasiliensis. - San-Blas, G (1982)
Yeast and mycelial particulate preparations of Paracoccidioides brasiliensis were subjected to the action of several detergents in an attempt to solubilize the glucan synthetase present in these preparations. This was achieved more successfully in the yeast membranes than in the mycelial ones. The enzymatic activity was greatly stimulated in the insoluble fractions upon treatment with some of the detergents used. The results suggest that the yeast and mycelial phases of P. brasiliensis may differ in the structures of their membranes and also in the characteristics of their glucan synthetases.